Perbedaan Leukosit , Suhu Tubuh Pada Pasien Stroke Haemoragik Dengan Non Haemoragik - Awan, Awan Hariyanto; Wulandari, Dewi; Ixora; Mimik (STIKES dan AKZI Karya Husada Kediri, 2024)
A stroke can have a physical and psychological impact, as well as infection due to blockage or rupture of blood vessels which can affect the body's immune system. The body's immune system that can be influenced by infection includes leukocytes and body temperature. This research method uses non-experimental correlational-cross-sectional. The population of this study is all adult patients who have had a stroke and are hospitalized in the stroke unit of the Regional Hospital. Dr. Soedomo Trenggalek with a sample size of 30 respondents met the inclusion and exclusion criteria. Normality test data analysis using Kolmogorov Smirnov, bivariate analysis of unpaired groups using the Man-Whitney test with a significance level ≤ 0.05. The results showed that there was no significant difference in leukocyte values ​​between hemorrhagic and non-hemorrhagic stroke patients (p) 0.902 > 0.05 and no significant difference in body temperature (p) 0.512 > 0.05 between hemorrhagic and non-hemorrhagic stroke patients. This study concludes that in hemorrhagic stroke patients and hemorrhagic stroke, there is no significant difference in the value of the infectious immune system in terms of the results of blood leukocyte examination and body temperature.